METODE TAGUCHI UNTUK PENINGKATAN KUALITAS MUTU PRODUK - Akhriyandi Wijanarta; Nur Salam; Dewi Anggraini (EPSILON: JURNAL MATEMATIKA MURNI DAN TERAPAN, 2014)
Costumers tend to choose a better product so that the quality improvement of a product is crucial. Quality control is a continuous process to ensure the quality of the products. The Taguchi method that was introduced by Dr. Genichi Taguchi in 1940 used to improve the quality of product and process as well as to reduce the production cost incurred by the company to minimize damage or defect in the products. The purpose of this research is to explain the procedures of Taguchi method to improve product quality. The results of the research show that the procedures using Taguchi method, are: the first step is counting the number of experiments and choosing the form of orthogonal arrays from the number of factors and levels that will be tested. The second step is conducting experiment and obtains data than calculating the mean value, and determining signal to noise rasio that is consistent to the quality characteristics of the experiment. The third step is analyzing experiment data using analysis of variance to determine factors that have a significant influence, then calculating the contribution value of each factor. If the contribution value of factor is smaller than the contribution value of error value then the factor will be pooling up. After getting the optimal alternative factors the fourth step is confirming experiment to examine the conclusion of the obtained data experiment. Furthermore, the five step is calculating the confidence intervals of response mean value betwen the prediction result of Taguchi method and the result of confirming experiment. After that, the sixth step is calculating Taguchi loss function to determine the amount of damage cost spent to improve the quality of product.